An endogenous mouse mammary tumor virus genome common in inbred mouse strains is located on chromosome 6. - Robbins, J M (1986)
We have examined EcoRI-restricted cellular DNA from mouse-hamster somatic cell hybrids. Results of this analysis show that the unit II mouse mammary tumor virus proviral genome is located on mouse chromosome 6. Restriction analysis of cellular DNA from (C3H/OuJ X Czech II) X Czech II backcross mice showed a strong linkage between unit II and Igk. The gene order of these markers on chromosome 6 relative to the Raf and Kirsten murine sarcoma virus ras-2 proto-oncogenes was established.